Dynamics of REL, RELA and IRF1 transcription factor expression in U937 macrophages after dioxin exposure - E. V. Kashina; D. Y. Oshchepkov; E. V. Antontseva; M. Y. Shamanina; D. P. Furman; V. A. Mordvinov (Вавиловский журнал генетики и селекции, 2017)
The aryl hydrocarbon receptor (AhR), a ligand- activated transcription factor, participates in a wide range of critical cellular events in response to endogenous signals or xenobiotic chemicals. 2,3,7,8-tetrachlorodibenzo-para-dioxin (TCDD) is one of the AhR ligands with a very high binding affinity for the AhR. TCDD is the most toxic among the dioxin xenobiotics and induces a broad spectrum of biological responses, including immunotoxicity and cancer. The complex ligand:AhR:ARNT functions as a transcription factor, binding to the dioxin responsive element (DRE) sequences in the regulatory regions of target genes. Macrophages are key regulators of the innate immune response, as well as one of the first types of cells which respond to chemical stress, so the study of the action of TCDD on these cells is important. Putative DREs were predicted using the SITECON software tool in the regulatory regions of the genes encoding transcription factors REL, RELA and IRF1 expressed in macrophages. Nuclear extract and total RNA were isolated from U937 macrophages treated with 10 nM TCDD (or 0.1 % DMSO as a control) for 1, 3 and 6 hours. The binding of the TCDD:AhR:ARNT transcription complex from the nuclear extract with double-stranded oligonucleotides containing the putative DREs was studied by the EMSA. Isolated RNA was used for the study of the TCDD-mediated alteration of gene expression levels using Real-time PCR with SYBR Green I. Obtained data demonstrate the functional activity of DREs in the IRF1, REL, RELA gene promoters via AhR signaling pathway.